Finite Element Analysis of a Buggy Car’s Suspension Arms for Off-Road Usage - Mohd Amir Shazwan, Hashim; Balaji P., Muthaiyah; Shaheerthana, Suresh; Muhammad Izzat Nor, Ma'arof; Girma, Tadesse Chala (INTI International University, 2020)
A buggy car is a versatile small-sized car without a roof that could be utilized in various terrains and purposes. This study designs a robust suspension arm for an off-road buggy-car. The study only focuses on the shape of the arm and its respective structural strength. Therefore, both the upper and lower arm were designed and simulated. The double wishbone suspension system was referred as the benchmark for this study. Furthermore, the BAJA SAE standard was followed in designing the new suspension arm. The CAD model was developed via the Inventor software and finite element analysis (FEA) was conducted via ANSYS software. With reference to the literature, the simulation was made by applying the load of 882.9 N onto the upper and lower suspension arm. The simulation results showed that the upper arm experienced 302.2 MPa and 5.5801 mm of deformation, whilst, the lower arm recorded the reading of an almost similar 302.2 MPa and 5.5731 mm deformation via FEA. These readings are however undesired, since it showed a relatively high bending stress and especially critical deformation for both the upper and lower arm. Conclusively, the design developed does not coincide with the goal of developing a robust suspension arm for an off-road buggy-car. Therefore, this design could serve as a platform for improvement for future studies.